Spectroscopic studies of Metal(II) complexes and application of the Ni(II) complexes to olefin oligomerisation catalysis - Bennett, Alison Margaret Anne (Department of Chemistry, 2016)
Complexes of some divalent first row transition metal ions with various ligands have been prepared. These included bis-complexes of β-ketoenolate ligands, nickel complexes of trialkylphosphine and nickel complexes containing phosphine and β-ketoenolate ligands, and finally, tris, bis and mono(ethylenediamine) complexes. Composition was ascertained by microanalysis and ¹H, ¹³C NMR of the diamagnetic complexes. In addition, the crystal structure of one of the nickel β-ketoenolate triethylphosphine complexes was determined. The infrared spectra of the above compounds have been examined over the range 4000-50 cm⁻¹ with a view to determining band assignments based on metal ion substitution, ligand substitution (for phosphine and β-ketoenolate complexes), ligand and metal ion isotopic labelling [for tris(ethylenediamine) complexes] and anion substitution (for phosphine and ethylenediamine complexes). In each case, spectra-structure correlations have been established and are discussed. Each of the nickel complexes prepared above was tested as a catalyst for the oligomerisation of 1-hexene. The experiments were carried out in batch at 40°C using toluene as solvent. Four different Lewis acid cocatalysts were tested and nickel : co-catalyst ratios of 1:1 and 1:10 were used. The effects of Lewis acid strength and concentration, nickel complex structure, a change in the donor chelating atom and the presence of phosphine ligands on the isomerisation, as well as the activity and selectivity of the oligomerisation reaction, are discussed. Two polymer-supported catalyst complexes have been prepared; the first,: by polymerisation of a nickel β-ketoenolate complex monomer and th, second, by binding a nickel β-ketoenolate phosphine complex to a polystyrene support through the phosphine ligand. The resultinJ polymers were extensively characterised by microanalysis, infrared, ¹H and ¹³C NMR, mass spectrometry, energy dispersive X-ray and thermal techniques. In the presence of a ten-fold excess of the ethylaluminium dichloride co-catalyst, each supported complex formed an active 1-hexene oligomerisation and isomerisation system. The activity and selectivity of each system have been compared to that of their respective monomers. Finally, the polymerised ,8-ketoenolate monomer was tested at various temperatures as a propene oligomerisation catalyst and the effect of temperature on activity and selectivity is discussed.